Chemical Oscillations With Sodium Perborate as Oxidant - Kurin-Csörgei, Krisztina; Poros-Tarcali, Eszter; Molnár, István; Orbán, Miklós; Szalai, István (Frontiers in Chemistry, 2020)
The peroxo compounds H2O2 and K2S2O8 represent one of the major constituents in many oscillatory chemical systems. In this contribution we demonstrate that beside H2O2 and S2O82– the sodium perborate (NaBO3·H2O) can act as alternative oxidizing agent in oscillatory reactions. So far the H2O2 has been successfully substituted with NaBO3 in two oscillators: in the BO3– – S2O32– – Cu(II) flow system potential and pH oscillations, in the strongly alkaline Cu(II)-catalyzed BO3– – SCN– batch reaction, which are rather different in their chemistry and dynamics, potential oscillations were observed. In spite of the significant differences in the oxidizing nature of H2O2 and NaBO3 we assume that the oscillatory cycle in the BO3– – substrate and in the H2O2 – substrate systems is similar in many aspects, therefore the numbers of this new subgroup of the oscillators may be considered to be borate-mediated H2O2 oscillators. Mechanisms are suggested and simulations are shown to describe the oscillatory behaviors observed in the perborate chemistry based oscillators by using the assumption that the oxidation reactions of the intermediates (HO)3B(OOH)⎻ and (HO)2B(OOH)2⎻ anions, which are dominant species in alkaline and neutral pH solutions of perborate, are much faster than that of H2O2.